Case Report: Simultaneously Developed Amyopathic Dermatomyositis and Autoimmune Sclerosing Cholangitis – a Coincidence or a Shared Immunopathogenesis? - Ledenko, Tomislav; Sorić Hosman, Iva; Ćorić, Marijana; Gagro, Alenka (Frontiers in Immunology, 2022)
Inflammatory rheumatic diseases (IRD) and autoimmune liver diseases (AILD) share many similarities regarding epidemiology, genetics, immunology and therapeutic regimens, so it is not surprising that approximately 20% of patients with AILD are diagnosed with an IRD as well. Clinical features and biochemical hallmarks of IRD and AILD often intertwine and cross diagnostic criteria. Therefore, the real distinction of underlying disorders in a patient with these comorbidities may be challenging. The present report is the first report of simultaneously developed juvenile dermatomyositis (JDM) and autoimmune sclerosing cholangitis (ASC) with both entities fulfilling the latest guidelines for a definite diagnosis. Both of these diagnoses are difficult to definitely establish since ASC has a similar serologic profile as autoimmune hepatitis and liver histological analysis is frequently non-specific, whereas clinically amyopathic JDM diagnosis depends mostly on classical dermatological symptoms, while the rest of the diagnostic criteria, including the necessity for skin or muscle biopsy and the presence of myositis specific antibodies, are still not uniformed. In spite of these challenges, our patient clearly met European League Against Rheumatism/ American College of Rheumatology classification criteria for CAJDM and The European Society for Pediatric Gastroenterology, Hepatology and Nutrition diagnostic criteria for ASC. Since elevated serum transaminases, the presence of serum antinuclear antibodies and hypergammaglobulinemia could be explained as a part of both JDM and ASC, the underlying pathophysiology remains debatable. Intriguingly, JDM and ASC share genetic predisposition including human leukocyte antigen allele DRB1*0301 and tumor necrosis factor α 308A allele. Furthermore, both humoral and cellular components of the adaptive immune system contribute to the pathogenesis of JDM and ASC. Moreover, recent findings indicate that the loss of the CD28 expression on T-cells plays a significant role in their pathogenesis along with the Th17 immune pathway. Despite these common features that suggest shared autoimmunity, AILD and autoimmune myositis are traditionally studied and managed independently. The lack of therapies that target the underlying cause results in a high rate of adverse events due to unspecific immunosuppressive therapy. Shared autoimmunity is an ideal area to develop new, targeted immunotherapy that would hopefully be beneficial for more than one disease.